Molecular testing in cancer - Jothy, Serge; Yousef, George M. (Springer New York, 2014)
Molecular Testing in Cancer provides a state of the art review of clinically relevant molecular pathology in cancer. The book provides a brief, easy to read review of commonly employed diagnostic molecular techniques including recently developed "next generation" analytic tools, and offers a system-based run-through of the utility of molecular testing in individual cancer types, as well as reviewing current markers in cancer diagnosis, prognosis, and management. The volume also provides a prospective for the future which includes recently characterized and emerging biomarkers. Written by experts in the field, Molecular Testing in Cancer serves as a useful and comprehensive resource for pathologists, hematologists, laboratory technicians and molecular scientists.